Commitment in Dating Relationships: The Influence of Religiosity and Peer Support - Paska, Paskalis Edwin I Nyoman; Laka, Laurensius (Bulletin of Counseling and Psychotherapy, 2024)
Premarital sex among students showed an increasing trend. Advances in communication technology were considered non-social factors thought to have contributed to this phenomenon. However, premarital sexual behaviour was indeed not only influenced by external factors. The research aimed to analyze the influence of religiosity and peer support on commitment in dating relationships. The research took samples from a population and used a questionnaire as the primary data collection tool. The target population for this research was students aged > 18 to 40 years who were categorized in the early adulthood range. The sampling technique was non-probability sampling because the respondents had characteristics that could not be randomly selected. Before the questionnaire was used, an instrument testing process was carried out, so the statement items contained in it contained a high discrimination index (item discrimination). Hypothesis testing used variance-based Structural Equation Modeling (SEM), namely Partial Least Squares (PLS-SEM), considering that there were variables with reflective and formative indicators in one research model. The results of data analysis showed that the two predictor variables (religiosity and peer support) simultaneously had a significant effect on commitment to a dating relationship, as evidenced by the value of Pr > F = 0.000 < α (α = 0.05). Likewise, partially, the t-statistics value of the religiosity variable was 4.807 > 1.96, and the t-statistics value of the peer support variable was 5.104 > 1.96. Thus, simultaneously and partially, these two predictor variables significantly affected student relationship commitment in early adulthood.